2018
DOI: 10.5194/isprs-archives-xlii-3-1299-2018
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Analysis of Modis Ndvi Time Series for Determining Hotspot of Land Degradation in Mongolia

Abstract: ABSTRACT:This study examines MODIS NDVI satellite imagery time series can be used to determine hotspot of land degradation area in whole Mongolia. The trend statistical analysis of Mann-Kendall was applied to a 16-year MODIS NDVI satellite imagery record, based on 16-day composited temporal data (from May to September) for growing seasons and from 2000 to 2016. We performed to frequency analysis that resulting NDVI residual trend pattern would enable successful determined of negative and positive changes in ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Remote sensing data have often been used to study the spatiotemporal characteristics of desertification in Mongolia [20,23,30,32,57,67] and the determination of desertification hotspots [33]. The indices derived from remote sensing data have been used to study the relationship between desertification and influencing factors.…”
Section: Research Methods Of Desertificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote sensing data have often been used to study the spatiotemporal characteristics of desertification in Mongolia [20,23,30,32,57,67] and the determination of desertification hotspots [33]. The indices derived from remote sensing data have been used to study the relationship between desertification and influencing factors.…”
Section: Research Methods Of Desertificationmentioning
confidence: 99%
“…Remote sensing data have been widely applied in the desertification monitoring in Mongolia. Previous studies on land desertification monitoring were mostly conducted based on the MODIS data [31][32][33], the United States National Oceanic and Atmospheric Administration Advanced Very High-Resolution Radiometer (NOAA-AVHRR) data [34], European Space Agency (ESA) land cover data [29], and Landsat data [35]. The spatial resolution of these data for the whole Mongolia study is generally low, which constrains the accuracy of the analysis results and an in-depth process understanding of desertification.…”
Section: Spatiotemporal Changes Of Desertificationmentioning
confidence: 99%
“…For instance, it is suggested that a higher value of spatial and spectral detail is appropriate in the case that the classified object is smaller than the spatial resolution of satellite image [35,36]. Therefore, values of spectral and spatial detail were set to 18 for all imagery (possible range: [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The size of objects is defined by the parameter of minimum segment size, which merges segments smaller than this criterion with their best fitting neighboring segment.…”
Section: Segmentationmentioning
confidence: 99%
“…The expansion of dirt road networks as a main type of linear infrastructure has become more apparent in recent decades, mainly due to the rapid economic development [6]. At the same time, approximately 76.8% of the Mongolian countryside is affected by land degradation while 6.1% of the land is extremely degraded due to human activities [7,8]. Both developments are related: The usage of dirt roads accelerates the land degradation process in Mongolian grasslands through vehicle travel that causes the destruction of the surface vegetation, soil compaction, loss of soil aggregation, changes in soil texture, partial or complete removal of the top layer of soil, and loss of soil organisms [9].…”
Section: Introductionmentioning
confidence: 99%